2020
DOI: 10.3389/fpsyg.2020.00659
|View full text |Cite
|
Sign up to set email alerts
|

Football Fans’ Emotions: Uncertainty Against Brand Perception

Abstract: Football is an industry driven by emotions. Fans experience many different emotions related to their teams. This paper aims to inspect how emotions impact attendance at football matches, examining whether football fans prefer to watch highly competitive matches or matches between good teams with star-players. The paper also considers behavioral and emotional differences of match spectators when brand-teams play away or at home. Importantly, we are also looking for the effects that the expectations of these emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
7
0
2
Order By: Relevance
“…We found consistent full mediations in Study 1, and partial mediations and direct effects in Study 2, among members of lowstatus groups. It is possible that the results in Study 2 may have been influenced by the unique characteristics of football context, such as, the strong emotional commitment that football invokes (see Shakina et al, 2020); the impact of participating in ritual gatherings (e.g., matches), of the symbols representative of the group (e.g., flags), and emotional entrainment, on identification and commitment with the group (Von Scheve et al, 2014). It may also have been influenced by other variables not included or controlled in the study, such as, the degree/intensity of rivalry between groups (being extremely intense between football teams, more than between Universities) that shape identities, attitudes and behaviors (e.g., Benkwitz and Molnar, 2012); degree of fan loyalty which reflects a persistent attitude resistant to change, and creates biases in cognitive processing and provides a guide to behavior (Funk and James, 2001); fanographics (i.e., variables that measure fans' relationship with the sport or club; e.g., time dedicated to the team; de Carvalho et al, 2015).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…We found consistent full mediations in Study 1, and partial mediations and direct effects in Study 2, among members of lowstatus groups. It is possible that the results in Study 2 may have been influenced by the unique characteristics of football context, such as, the strong emotional commitment that football invokes (see Shakina et al, 2020); the impact of participating in ritual gatherings (e.g., matches), of the symbols representative of the group (e.g., flags), and emotional entrainment, on identification and commitment with the group (Von Scheve et al, 2014). It may also have been influenced by other variables not included or controlled in the study, such as, the degree/intensity of rivalry between groups (being extremely intense between football teams, more than between Universities) that shape identities, attitudes and behaviors (e.g., Benkwitz and Molnar, 2012); degree of fan loyalty which reflects a persistent attitude resistant to change, and creates biases in cognitive processing and provides a guide to behavior (Funk and James, 2001); fanographics (i.e., variables that measure fans' relationship with the sport or club; e.g., time dedicated to the team; de Carvalho et al, 2015).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…We emphasize that the discrepancies mentioned above may depend on the approach adopted to carry out the analysis and the contexts examined. Specifically, (i) the amateur sport could differ substantially from the professional sport when the ability of athletes to respond to external stimuli is concerned [ 13 - 15 ]; (ii) fans' reactions could depend on the sport, season, and even the match or event in question [ 16 ]; (iii) the economic condition of the clubs could affect the performance of athletes [ 17 ]; (iv) supporters can often express disappointment during a match or sporting performance [ 2 ]; and (v) other psychological, social, and cultural variables could unpredictably alter sports performance [ 18 - 20 ]. Since the enormous damage caused by COVID-19 from a psychological point of view falls into the latter category of bias [ 21 , 22 ], it is necessary to interpret all the evidence found with caution.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that attendance would be maximized when the ex-ante probability of the home team winning is twice (66%) the chance of the visiting team to win the game, implying an inverted U-shaped curvilinear relationship. Conversely, Shakina et al (2020) reported the U-shape effect of the uncertainty of sport outcomes on attendance [49]. Greater attendance is expected at low and high levels of uncertainty than at the middle level of uncertainty.…”
Section: Competitive Balance and Sormentioning
confidence: 99%
“…However, over the years, the UOH stating that spectators prefer games with uncertain outcomes has been debated under various conditions [34,46]. The UOH has been challenged by alternative specifications such as the effects of the home team's strength [46,47] and absolute team strength [48,49] on live attendance. Shakina et al (2020) tested the UOH against the brand-team effect and found that fans prefer to watch good team play (including star players or brand teams) rather than highly competitive matches [49].…”
Section: Competitive Balance and Attendancementioning
confidence: 99%